Friend or Foe? Perceptions of Qatar in the Israeli Online General and Sports Press. Issue 5 (2nd September 2016) - Galily, Yair; Yarchi, Moran; Samuel-Azran, Tal; Cohen, Rona
Abstract: The current paper is looking into the way in which Qatar's investment in sport, both directly and indirectly, is being perceived by the Israeli press. In order to accomplish the task set above, a content analysis of Qatar's media coverage in the Israeli online press was conducted. Our analysis includes 1199 articles appearing in the mainstream online Israeli press and the findings point out to an interesting trend; there are significant differences between sport related stories, which present a political context and those who do not deal with politics which are significantly more supportive of Qatar.